2018
DOI: 10.1002/cctc.201702005
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Regulation of an Autocatalytic Wave of Spatially Propagating Enzymatic Reactions

Abstract: Bioinspiration is an attractive way to develop new robust chemistry. In biological cell, chemical reactions form complex networks (e.g. signaling and metabolic) that communicate with each other and control cell division, growth, and interaction with environment. Thus, combining multiple chemical subsystems into a single network is an attractive way to design a chemical system with new functions. In this paper, we combined two chemical networks: i) a photocatalytic oxidation/ reduction on TiO2 particles, and ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Photocatalytic reduction [107] of noble metal particles on titania core [95] leads to dual-wavelength responsiveness: in the UV to near-IR regions of electromagnetic spectrum. It is possible to regulate photocatalytically (auto-catalytic) waves of enzymatic reactions [108], switch biofilm fluorescence [109], build a platform for a chemical logic device [110], and perform sustainable diagnostics [111][112][113]. The trend in the field of encapsulated systems is to combine different functions in one capsule matrix.…”
Section: Corrosion Protection Of the Coatingsmentioning
confidence: 99%
“…Photocatalytic reduction [107] of noble metal particles on titania core [95] leads to dual-wavelength responsiveness: in the UV to near-IR regions of electromagnetic spectrum. It is possible to regulate photocatalytically (auto-catalytic) waves of enzymatic reactions [108], switch biofilm fluorescence [109], build a platform for a chemical logic device [110], and perform sustainable diagnostics [111][112][113]. The trend in the field of encapsulated systems is to combine different functions in one capsule matrix.…”
Section: Corrosion Protection Of the Coatingsmentioning
confidence: 99%
“…The approach described herein can be used in many applications where targeted and delayed switching and light upconversion are required. Such complex materials are very important for complex chemical network integration with biological networks such as enzymatic networks, 38 bacterial quorum sensing, 89 and synthetic biology, 90 suggesting them to be one working reaction network.…”
Section: ■ Logic Gatesmentioning
confidence: 99%
“…91 Stimuli-responsive biointerfaces open perspectives to smart materials for tissue engineering. Thus, the formation of trypsin from its precursor trypsinogen was chosen as an example of the pH-sensitive autocatalytic enzymatic reaction and was studied on the TiO 2 / PSS/PEI hybrid and TiO 2 surface as a control 38 (Figure 8). The results indicated that the acidification of the media near pristine TiO 2 was the most possible explanation of trypsin suppressed formation in comparison to the hybrid system.…”
Section: Langmuirmentioning
confidence: 99%
See 2 more Smart Citations